2011
DOI: 10.1002/pon.1942
|View full text |Cite
|
Sign up to set email alerts
|

The process and effect of supportive message expression and reception in online breast cancer support groups

Abstract: Objective To better understand the process and effect of social support exchanges within computer-mediated social support (CMSS) groups for breast cancer patients, this study examines 1) the dynamic interplay between emotional support giving and receiving and 2) the relative effects of emotional support giving and receiving on patients’ psychosocial health outcomes. Methods Data was collected from 177 patients who participated in online cancer support groups within the Comprehensive Health Enhancement Suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(126 citation statements)
references
References 56 publications
(75 reference statements)
2
118
0
2
Order By: Relevance
“…People use CMC to engage in supportive interactions with both established relational partners and strangers (Rains & Keating, 2011;Walther & Boyd, 2001;Wright, 2000). Engaging in supportive interactions online elicits emotional improvement and decreased levels of depression, loneliness, and stress (Kim et al, 2012;van Uden-Kraan, Drossaert, Taal, Seydel, & Van De Laar, 2009;Wright, 2000). In fact, some people indicate that they are more satisfied with the support they receive online than FtF (Wright, 1999).…”
Section: Cmc As a Channel For Supportive Communicationmentioning
confidence: 99%
“…People use CMC to engage in supportive interactions with both established relational partners and strangers (Rains & Keating, 2011;Walther & Boyd, 2001;Wright, 2000). Engaging in supportive interactions online elicits emotional improvement and decreased levels of depression, loneliness, and stress (Kim et al, 2012;van Uden-Kraan, Drossaert, Taal, Seydel, & Van De Laar, 2009;Wright, 2000). In fact, some people indicate that they are more satisfied with the support they receive online than FtF (Wright, 1999).…”
Section: Cmc As a Channel For Supportive Communicationmentioning
confidence: 99%
“…While people use OHCs for a wide range of needs, obtaining psychosocial support is one of the key benefits of engagement in OHCs [3,4]. Research has found that such support can help patients adjust to the stress of living with and fighting against their diseases [5,6,7] and is a consistent indicator of survival [8].…”
Section: Introductionmentioning
confidence: 99%
“…Also Kim et al (2012) described the process and effect of social support exchanges within computer-mediated social support groups for breast cancer patients, showing that receiving and giving exchanges play positive, but different, roles in predicting psychosocial health outcomes.…”
Section: Research-article2017mentioning
confidence: 99%